Effectiveness of road maintenance management in Klang district [electronic resource] - 410166 Mohd. Zaidi Zainal; Rosli Mohamad Zin, supervisor (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2007